What Happens in Parliament Stays in Parliament? Newspaper Coverage of National Parliaments in EU Affairs*. (26th November 2017) - Auel, Katrin; Eisele, Olga; Kinski, Lucy
Abstract: The role of national parliaments in EU matters has become an important subject in the debate over the democratic legitimacy of the European Union. Yet despite a remarkable increase in parliamentary involvement in EU affairs, the added value in terms of democratic legitimacy will remain limited if citizens are not aware of their activities. Given that citizens mainly experience politics through the media, the aim of the paper is therefore to explore whether and under what conditions parliamentary involvement in EU matters is visible in national newspapers. The paper draws on two quantitative datasets covering parliamentary EU activities and relevant newspaper articles in seven Member States between 2010 and 2013. Results suggest that the efforts of active parliaments pay off. In addition, conflict within government coalitions over EU issues and greater salience of EU politics in public opinion increase coverage while, surprisingly, both public and parliamentary euroscepticism do not.